Natural theology - McGrath, A (University of St Andrews, 2022)
This article explores the biblical foundations and historical development of natural theology, noting in particular its relationship with the emergence of the natural sciences. After considering some questions of definition, the biblical foundations of natural theology are considered, followed by a detailed historical engagement with its development within the theological tradition during the patristic period, the Middle Ages, the Renaissance and Reformation, and the early modern period. The concept of ‘physico-theology’, which emerged during the seventeenth century, is of particular significance in highlighting the close interaction between natural theology and the emerging natural sciences. Although early modern natural theology tended to focus on the physical sciences, interest in the potential of the biological world for natural theology became increasingly important, and is perhaps seen at its zenith in William Paley’s Natural Theology (1802). Yet Darwin’s theory of evolution through a process of natural selection called into question Paley’s idea of a divine watchmaker, suggesting that complex biological structures emerged through the unguided natural process of evolution. The challenges raised by Darwin and his successors for natural theology are carefully evaluated. Yet although Darwin raised some difficulties for traditional forms of natural theology, the growing twentieth-century realization that the universe came into existence with properties that seemed to be fine-tuned for life created new interest in this approach. These approaches are noted, before the article concludes with some wider reflections on the interaction between natural theology and the sciences, particularly the possibility that natural theology might serve as a bridge between science and religion.